Distància lingüística i classificació de varietats dialectals - Clua Julve, Esteve (Caplletra. Revista Internacional de Filologia, 1999)
Over the last two decades there has been a growth of quantitative studies of linguistic variation, aimed at overcoming the potential arbitrariness of dialectal divisions based on qualitative criteria. However, dialect measuring methods have also proved incomplete, which has endangered both the adequacy of the results obtainedand their apparent objectivity. In order to solve the problem, this paper proposes a classification of dialectal varieties based on the notion of linguistic distance. The main feature of our proposal which we have applied to the classification of Valencian varieties, is the fact that it is based on a set of representative, homogeneous data -moreprecisely, on flexive morphology; thus, the treatment of variation results from a consistent linguistic analysis and, through statistical control measures, it is possible to check the reliability of the classifications obtained.